Capabilities of Forensic Fire Investigation in Evaluating the Quality of Fireproofing of Structures Built with Wood and Wood Based Materials - Yurii F. Mukhin (Теория и практика судебной экспертизы, 2017)
The paper analyzes the state of the problem of evaluating the quality of fire retardant treatment of wood and wood based materials in the course of forensic fire investigation. It addresses the following issues: examination of fireproofing paperwork, collection of samples at the site of the incident, and methods for testing the quality of fire retardant treatment of wood.